TRPV1-Estradiol Stereospecific Relationship Underlies Cell Survival in Oxidative Cell Death - Ramírez-Barrantes, Ricardo; Carvajal-Zamorano, Karina; Rodriguez, Belen; Cordova, Claudio; Lozano, Carlo; Simon, Felipe; Díaz, Paula; Muñoz, Pablo; Marchant, Ivanny; Latorre, Ramón; Castillo, Karen; Olivero, Pablo (Frontiers in Physiology, 2020)
17β-estradiol is a neuronal survival factor against oxidative stress that triggers its protective effect even in the absence of classical estrogen receptors. The polymodal transient receptor potential vanilloid subtype 1 (TRPV1) channel has been proposed as a steroid receptor implied in tissue protection against oxidative damage. We show here that TRPV1 is sufficient condition for 17β-estradiol to enhance metabolic performance in injured cells. Specifically, in TRPV1 expressing cells, the application of 17β-estradiol within the first three hours avoided H2O2-dependent mitochondrial depolarization and the activation of caspase 3/7 protecting against the irreversible damage triggered by H2O2. Furthermore, 17β-estradiol potentiates TRPV1 single channel activity associated with an increased open probability. This effect was not observed after the application of 17α-estradiol. We explored the TRPV1-Estrogen relationship also in primary culture of hippocampal-derived neurons and observed that 17β-estradiol cell protection against H2O2-induced damage was independent of estrogen receptors pathway activation, membrane started and stereospecific. These results support the role of TRPV1 as a 17β-estradiol-activated ionotropic membrane receptor coupling with mitochondrial function and cell survival.